Kashmir : Paradise on Earth or a Nuclear Flashpoint - Schuurmans, Laura (Indonesia Kashmir Solidarity Forum, 2010)
Jammu and Kashmir is one of the most beautiful places on earth and has often been described by poets and travellers as paradise on earth. However, following the partition of India in 1947, the region has become a site of conflict between India and Pakistan and is now a potential nuclear flashpoint in Asia. Thus, in this article, the author examines the genesis of the Kashmir dispute and tries to ascertain the legality of the accession of Jammu and Kashmir to India.
Include Map, Illustration and References
Keywords: India--Jammu and Kashmir -- Pakistan -- India -- Diplomatic relations -- Politics and government